2014
DOI: 10.1007/s00213-014-3662-7
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional psychiatry: reward dysfunction and depressive mood across psychiatric disorders

Abstract: RationaleA dimensional approach in psychiatry aims to identify core mechanisms of mental disorders across nosological boundaries.ObjectivesWe compared anticipation of reward between major psychiatric disorders, and investigated whether reward anticipation is impaired in several mental disorders and whether there is a common psychopathological correlate (negative mood) of such an impairment.MethodsWe used functional magnetic resonance imaging (fMRI) and a monetary incentive delay (MID) task to study the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 74 publications
7
146
2
Order By: Relevance
“…Thus, reward system pathology may contribute to clinical reward dysfunction across multiple psychiatric disorders. Further confirmation comes from an important recent study by Hägele et al (2014), which demonstrated that depressive symptoms are associated with a similar blunting of reward responses in a large sample of patients with diverse diagnoses.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, reward system pathology may contribute to clinical reward dysfunction across multiple psychiatric disorders. Further confirmation comes from an important recent study by Hägele et al (2014), which demonstrated that depressive symptoms are associated with a similar blunting of reward responses in a large sample of patients with diverse diagnoses.…”
Section: Discussionmentioning
confidence: 84%
“…However, only one study to our knowledge has examined reward-related signaling in bipolar depression: Chase et al (2013) who did not find differences in ventral striatum prediction error responses between controls and subjects with bipolar or unipolar depression. Additionally, an important recent study by Hägele et al (2014) demonstrated that depressive symptoms are associated with a similar blunting of reward responses in a large and diverse sample of subjects including unipolar depression, bipolar disorder, ADHD, alcoholism, and schizophrenia.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In humans, neuroimaging has been widely used to study brain signals related to reward anticipation. Functional MRI experiments probing reward anticipation in the ventral striatum with MID tasks reveal decreased striatal activation in drug-naïve and unmedicated schizophrenia patients Hägele et al, 2015;Juckel et al, 2006b) as well as in participants at high clinical risk for psychosis (Juckel et al, 2012;Wotruba et al, 2014). The degree of reduced reward anticipation is linked to symptom severity (Juckel et al, 2006a;Kring and Barch, 2014;Nielsen et al, 2012) and altered dopamine activity, as suggested by the observation that treatment with atypical antipsychotics partially normalizes ventral striatal dysfunction in schizophrenia (Nielsen et al, 2012;Walter et al, 2009).…”
Section: Reward Anticipation Is Reduced In Schizophreniamentioning
confidence: 97%
“…Such a perspective could suggest a common pathophysiologic mechanism for related and often co-occurring psychiatric disorders. One example of a transdiagnostic perspective comes from a recent study by Hägele et al (2015) which used the same MID task in patients with schizophrenia, major depression, alcohol addiction, bipolar manic episode, or ADHD and found commonly reduced reward anticipation signals in schizophrenia, major depression and alcohol addiction.…”
Section: Reward Anticipation Is a Transdiagnostic Feature In Psychiatmentioning
confidence: 99%